Effect of Motivation on Employee Performance in Oke-Ogun Polytechnic, Saki Oyo State, Nigeria - Salahu, Olayinka Moshood; Lawal , Yusuf Birisan; Mosaudu, Kunle Adedokun (Kashere Journal of Politics and International Relations, 2025)
The Employee performance is a vital driver of institutional success, and motivation plays a critical role in enhancing employees' productivity and job satisfaction. This study aims to examine how various motivational factors affecting employee performance of non-academic staff at the polytechnic. This involves beginning with a quantitative method (e.g. questionnaire results) and followed by a qualitative method involving detailed exploration with a few individuals. The quantitative data was analyzed using Statistical Packages for Social Sciences (SPSS) to determine correlations between motivation variables and performance outcomes. The interview responses were thematically presented and analysed. The findings reveal that motivation has a substantial impact on employees' performance at Oke-Ogun Polytechnic such as staff training development and fringe benefits (such as salary increments, bonuses, and allowances were found to have a significant influence on employee productivity, particularly for non-academic staff. Despite these positive correlations, the study also identified challenges related to motivation at Oke-Ogun Polytechnic. Some employees expressed dissatisfaction with the existing motivational strategies, citing insufficient career advancement opportunities, delayed promotions, and the lack of regular feedback from management. The study recommends that management should consider implementing regular performance reviews and feedback mechanisms to align employee goals with organizational objectives.